Anaisis Inklusi Keuangan Bagi Pelaku Umkm Di Kabupaten Ogan Komering Ulu: Studi Kasus Nasabah Bank Syariah Indonesia Cabang Baturaja - Sri Merzarani; Muhammad Rusdi; Rika Lidyah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of this study, among others, is to anayze the implementation of financia inclusion at Bank Syari`ah Indonesia (BSI) Baturaja Branch in the MSME sector through BSI Kur Micro financing for the people of Kab. OKU and To anayze the development of financial inclusion of Bank Syariah Indonesia (BSI) Baturaja branch in the MSME sector through BSI Kur Micro financing for the people of Kab. OKU. The author uses a quaitative descriptive research method, namely quaitative research, which seeks financia inclusion in Bakan Syari`ah Indonesia (BSI) Cabang Baturaja.. The technique of collecting/collecting quaitative data is basicaly tentative in terms of user anaysis is determined by the context of research. ahan dan gambaran data who was embarrassed to get. The data collection technique that the authors use in this research is preliminary (interview) in documentation. The results of this study are that Bank Syariah Indonesia has implemented maximum financia inclusion in terms of capita investment using BSI Kur Mikro financing, they have capitaized on BSI Kur Mikro financing products. According to them, this product has come back quite well and helps each other for sellers who have micro and smal businesses that require financing fasifications.